2021
DOI: 10.1039/d0ra09240a
|View full text |Cite
|
Sign up to set email alerts
|

Effective oil–water mixture separation and photocatalytic dye decontamination through nickel-dimethylglyoxime microtubes coated superhydrophobic and superoleophilic films

Abstract: The nickel-dimethylglyoxime microtubes were synthesized by a facile coprecipitation method. The as-prepared superhydrophobic and superoleophilic films showed excellent oil–water separation efficiency and effective photocatalytic degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Pressure experiments have shown that the M ... M interactions account also for the compressibility of these structures and the pressure-dependent changes of colour and electronic properties [3,4,8,12,[26][27][28][29][30][31]. These virtually insoluble metal ... metal stacked solids are the basis for applications of the three compounds [M(Hdmg) 2 ] (M = Pt, Pd, Ni) for the extraction or removal of these elements [32][33][34][35], as components of solid catalysts [36][37][38][39][40], as solid but easily evaporable precursors [37][38][39][40][41][42][43][44][45][46][47], and in optical devices (e.g., pressure calibrants/indicators) [3,4,12,[26][27][28][29][30][31][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure experiments have shown that the M ... M interactions account also for the compressibility of these structures and the pressure-dependent changes of colour and electronic properties [3,4,8,12,[26][27][28][29][30][31]. These virtually insoluble metal ... metal stacked solids are the basis for applications of the three compounds [M(Hdmg) 2 ] (M = Pt, Pd, Ni) for the extraction or removal of these elements [32][33][34][35], as components of solid catalysts [36][37][38][39][40], as solid but easily evaporable precursors [37][38][39][40][41][42][43][44][45][46][47], and in optical devices (e.g., pressure calibrants/indicators) [3,4,12,[26][27][28][29][30][31][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…These results confirm the formation of NDMG, and they are in accordance with literature data. [18][19][20] XRD analysis of NDMG in Figure 1(b) shows a diffraction peak with high intensity at 2θ = 9.9°due to the (110) plane, and it confirms the synthesis of a highly crystalline structure. 20 The XRD peaks at the 2θ values of 10.6°, 14.9°, 17.1°, 23.6°, 24.2°, 25.3°, 26.7°, 27.5°, 28.1°, 29.2°, 32.61°, 34.5°, 35.6°, 38.4°, 43.67°, and 46.08°can be referred to as the ( 200), ( 211), ( 130), ( 002), ( 510), ( 112), ( 022), ( 521), ( 240), ( 710), (150), and (242) planes, respectively, and they indicate the formation of NDMG with good purity.…”
Section: Characterization Of Ndmg and Mpmentioning
confidence: 97%
“…The char residue at 750°C is 8.4%, which can be attributed mainly to the formation of NiO and carbon. 18,20 The control sample attains T 10% , T 50% , T 1max , and T 2max at 336, 389, 371, and 436°C, and it leaves 5.0% as a char residue at 750°C. The TGA curve of pure cotton illustrates that the main pyrolysis occurs between 300°C and 500°C and is accompanied by 83.7% weight loss.…”
Section: Morphology Of Control and Treated Cfsmentioning
confidence: 99%
See 2 more Smart Citations